Hormonal replacement theray and uterus carcinomas - Opala, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
In this article the effects of hormone replacemnt therapy on endometrial cancer risk are reviewed. In pathogenesis of endometrial cancer central role, exept hiperestrogenism and progesteron deficiency, plays FSH, LH, prolactin, insulin, IGF-I as well. Smoking moderates the risk associated with endometrial cancer among women at greatest risk, specifically women who are obese or who use postmenopausal hormones.